The effect of estrogen synthesis inhibition on hippocampal memory. (June 2015) - Bayer, Janine; Rune, Gabriele; Schultz, Heidrun; Tobia, Michael J.; Mebes, Imke; Katzler, Olaf; Sommer, Tobias
Highlights: Estradiol depletion specifically impaired hippocampus-dependent memory. Estradiol depletion tended to decrease memory-related hippocampal activity. Estradiol depletion increased memory-related activity in prefrontal areas. The increased prefrontal activity reflects most likely a compensatory mechanism. Summary: 17-Beta-estradiol (E2) facilitates long term-potentiation (LTP) and increases spine synapse density in hippocampal neurons of ovariectomized rodents. Consistent with these beneficial effects on the cellular level, E2 improves hippocampus-dependent memory. A prominent approach to study E2 effects in rodents is the inhibition of its synthesis by letrozole, which reduces LTPs and spine synapse density. In the current longitudinal functional magnetic resonance imaging (fMRI) study, we translated this approach to humans and compared the impact of E2 synthesis inhibition on memory performance and hippocampal activity in post-menopausal women taking letrozole ( n  = 21) to controls ( n  = 24). In particular, we employed various behavioral memory paradigms that allow the disentanglement of hippocampus-dependent and -independent memory. Consistent with the literature on rodents, E2 synthesis inhibition specifically impaired hippocampus-dependent memory, however, this did not apply to the same degree to all of the employed paradigms. On the neuronal level, E2 depletion tended to decrease hippocampal activity during encoding, whereas it increased activity in the anterior cingulate and the dorsolateral prefrontal cortex. We thus infer that the inhibition of E2 synthesis specifically impairs hippocampal functioning in humans, whereas the increased prefrontal activity presumably reflects a compensatory mechanism, which is already known from studies on cognitive aging and Alzheimer's disease.